Development Foundations of Interactive Media: The Role of Socio-Educational Environment and Paperless Learning as Predictors of Eco-Digital Literacy - Sima Fatmawati; Yulina Ismiyanti; Luqman Rohmad Maghribi (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
The rapid transformation of digital education has increased the need to integrate technological competence with environmental responsibility in primary education. Previous studies on digital literacy and environmental education have generally been conducted separately and remain predominantly technocentric, with limited attention to socio-educational interaction and sustainable digital practices in developing eco-digital literacy. This study aims to examine the relationship between the socio-educational environment, paperless learning, and eco-digital literacy among primary school students. A quantitative correlational design was applied involving 135 students from digitally integrated primary schools in West Java, Indonesia. Data were collected using Likert-scale questionnaires and analyzed through Pearson correlation and multiple linear regression using SPSS 27.0. The findings revealed that the socio-educational environment had a stronger positive relationship with eco-digital literacy (r = 0.64, p < 0.01) than paperless learning (r = 0.51, p < 0.01). Regression analysis showed that the socio-educational environment was the strongest predictor (β = 0.52, p < 0.001), while paperless learning also contributed significantly (β = 0.29, p < 0.01). The study highlights that paperless learning alone is insufficient without teacher guidance, social interaction, and a sustainability-oriented school culture.